2015
DOI: 10.1016/j.otsr.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoblastic differentiation and bone formation in co-culture of human bone marrow mesenchymal stromal cells and peripheral blood mononuclear cells with exogenous VEGF

Abstract: Our study demonstrates that the in vitro ALP activity and mineralization of human BM-MSCs is more efficient in the presence of PB-MNCs, and exogenously added VEGF further enhances the stimulatory effect. This indicates that PB-MNCs could be a potential cell source in development of co-culture systems for novel tissue engineering applications for enhanced bone healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The results of this study also showed that KLF2 + stemness‐maintained hMSCs enhanced osteogenesis more effectively in long‐term culture. Several previous studies have investigated the osteogenic effect between endothelial and osteoblastic cells and identified the crucial role of VEGF . Indeed, VEGF‐A was shown to act as a pivotal regulator in angiogenesis by specific binding to cell‐surface receptors, and also to play an essential role in bone formation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study also showed that KLF2 + stemness‐maintained hMSCs enhanced osteogenesis more effectively in long‐term culture. Several previous studies have investigated the osteogenic effect between endothelial and osteoblastic cells and identified the crucial role of VEGF . Indeed, VEGF‐A was shown to act as a pivotal regulator in angiogenesis by specific binding to cell‐surface receptors, and also to play an essential role in bone formation .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have investigated the osteogenic effect between endothelial and osteoblastic cells and identified the crucial role of VEGF. 33,[42][43][44] Indeed, VEGF-A was shown to act as a pivotal regulator in angiogenesis by specific binding to cell-surface receptors, 24,45 and also to play an essential role in bone formation. [46][47][48] Previous studies examined the roles of VEGF both in vivo and in vitro and showed that blocking the action of VEGF inhibited osteogenesis.…”
Section: Stemness-and Osteogenesis-related Gene-expression Profiles Inmentioning
confidence: 99%
“…[6][7][8][9] Improved engineered vasculature would allow ischemic and traumatic tissue defects to be treated more effectively and efficiently. [9][10][11][12][13] The insulin super-family is composed of 10 members in mammals, insulin, 2 insulin-like growth factors, 3 relaxin proteins, and 4 insulinlike peptides.…”
Section: Vascular Endothelial Growth Factor (Vegf) a And Fibroblast mentioning
confidence: 99%
“…In addition to MNC‐derived EPCs, MSCs have been shown to differentiate into endothelial cells (Table ). In a previous study, MSCs cultured with exogenous VEGF did not differentiate into endothelial cells (Joensuu et al, ) and the sprouting tube‐forming cells in the cocultures were positive for TRACP, an enzyme, which is expressed by the cells of monocyte‐lineage (Joensuu et al, ) indicating that endothelial cells in the MSC‐MNC cocultures probably differentiated from MNC‐derived EPCs instead of MSCs. However, the origin of each mature cell type has not been fully demonstrated in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…It was previously shown that PB-MNCs can differentiate into endothelial cells in MSC-MNC cocultures without exogenously supplied growth factors (Joensuu et al, 2011) and data have demonstrated that MSCs produce proangiogenic factors, such as VEGF and fibroblast growth factor 2 (FGF-2) in a differentiation-dependent manner (Hoch, Binder, Genetos, & Leach, 2012). By contrast, recent results show that in MSC-MNC cocultures the osteoblastic differentiation of human BM-MSCs is enhanced and further potentiated by exogenous VEGF (Joensuu et al, 2015). Taken together, all these data suggest isolated from a 5-ml aspirate of iliac bone marrow from a healthy donor.…”
mentioning
confidence: 99%